Correction: Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2026)

Marine distribution and habitat use by Snow Petrels Pagodroma nivea in East Antarctica throughout the non-breeding period - Benjamin Viola; Barbara Wienecke; Cara-Paige Green; Stuart Corney; Ben Raymond; Colin Southwell; Michael D. Sumner; Patti Virtue; Simon Wotherspoon; Louise Emmerson (Frontiers in Marine Science, 2023)
The relationships between flying Antarctic seabirds and their at-sea environments remain poorly understood, particularly outside of the breeding season. Improving our knowledge of how these marine predators use their habitat is a critical step towards conservation of these species. We tracked 27 adult Snow Petrels from two large breeding colonies in East Antarctica during the Austral winter (non-breeding period) – when they are primarily at sea away from their nesting sites. During this time, Snow Petrel habitat use was most associated with bathymetry (> 5000 m), low sea-surface height, relatively close distance to the southern boundary of the Antarctic Circumpolar Current, relatively close distance to the ice-edge, relatively high sea-ice concentration, and low sea-surface temperature. Individuals displayed various movement patterns: 20 birds occupied overlapping winter areas that ranged broadly (up to 2000 km) from their breeding sites. The remaining birds ventured far beyond their breeding sites – reaching a maximal distance from the colony of 5,268 km. One individual circumnavigated Antarctica. Daily activity patterns were related to day length, with peak activity occurring near dawn and dusk. Nocturnal activity increased from March until August/September. Key results reveal and depict Snow Petrel habitat maps for the non-breeding period in the East Antarctic region.

L-lactic and 2-ketoglutaric Acids, Odors from Human Skin, Govern Attraction and Landing in Host-Seeking Female Aedes aegypti Mosquitoes - Benjamin D. Sumner; Brogan Amos; Jan Bello; Ring T. Cardé (Journal of Insect Behavior, 2022)
Aedes aegypti , presented with a source of L-lactic and 2-ketoglutaric acid in a wind-tunnel bioassay, takeoff, fly upwind, and land on the odorant substrate at rates comparable to those exhibited by mosquitoes presented with a skin-odor stimulus. Addition of carbon dioxide decreased takeoff latency but was not required to elicit upwind flight nor landings. Ketoglutaric acid, a recently identified component of human skin odor, combined with lactic acid elicits the full repertoire of mosquito host-seeking behaviors.

Primacy of Human Odors Over Visual and Heat Cues in Inducing Landing in Female Aedes aegypti Mosquitoes - Benjamin D. Sumner; Ring T. Cardé (Journal of Insect Behavior, 2022)
Although human skin odor is thought to be the cue that anthropophilic mosquitoes use to discriminate us from other potential hosts, the precise details of how they use skin odor to find and land on a human is unclear. We found that Aedes aegypti land on a source of skin odor without a co-located visual cue. By collecting human odor on glass beads and using identical glass beads to visually conceal skin odor and heat cues, we were able to study mosquito landing on skin odor, heat, and visual cues separately. Landing is necessary for blood feeding which is a required behavior for the Aedes aegypti life cycle as well as the behavior responsible for the epidemiological impact of mosquitoes. Therefore, we consider it to be the diagnostic measure of the importance of a host cue. In two-choice tests, a skin odor source had the highest valence for landing, followed by a combination of heat and a visual cue, and finally heat and visual cues presented separately. We also measured the durations of the landings, though no significant differences were found.